Implementation of a digital marketing strategy for the “pantanera store” of the pantanos de Villa wetland - Chorrillos, Lima, Peru - Rubin-Yajahuanca, Leonardo (2023)
Th e implementation of the digital marketing strategy for the “Pantanera Store” in the Pantanos de Villa wetland, Lima, Peru was evaluated. A semi-structured survey was carried out on the target audience made up of two segments: people who reside in the districts near the wetland and are interested in tourism and the environment, and a general public that is made up of young people with access to a university higher educational level. Th e results of the digital marketing strategy indicate that the store and the online catalog of the “Pantanera Store” products must be easy to use. Payment options must be secure and easy to access. Online payment must be made through affi liation with secure banks in the national market, and with applications such as Yape and Plin. Th e proposal to implement a digital marketing strategy for the “Pantanera Store” is based on the interaction of visitors to the Pantanos de Villa wetland and digital media, such as social networks. Th is implementation will help obtain greater opportunities, promotions, and advantages for the public. Finally, mechanisms must be facilitated to achieve greater sales, achieving greater interaction, and loyalty of the public concerning the “Tienda Pantanera”.